2020
DOI: 10.23887/jet.v4i3.27794
|View full text |Cite
|
Sign up to set email alerts
|

Team Assisted Individualization Model Assisted by Effective Ludo Media Improving Student Learning Outcomes

Abstract: The low competence of mathematical knowledge caused by the lack optimal use of the learning model makes it difficult for students to understand the learning material. The purpose of this study was to analyze the effectiveness of the Team Assisted Individualization model assisted by Ludo media on learning outcomes in terms of the problem-solving ability of fraction material. This type of research was a quantitative study using pre-experimental design in the form of a one-group pretest-posttest design. The numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
2
0
2
Order By: Relevance
“…Similar conclusions were also found by Arrahim, et al [21], who highlighted the improvement of students' conceptual understanding at the elementary school level through the application of the TAI model. Furthermore, Wilujeng, et al [43], in their research, reported that the TAI model equipped with Ludo media was effective in improving learning outcomes in fraction materials. The results of Putri and Fitria [22] also showed a positive impact on student learning outcomes through the TAI learning model.…”
Section: Discussionmentioning
confidence: 99%
“…Similar conclusions were also found by Arrahim, et al [21], who highlighted the improvement of students' conceptual understanding at the elementary school level through the application of the TAI model. Furthermore, Wilujeng, et al [43], in their research, reported that the TAI model equipped with Ludo media was effective in improving learning outcomes in fraction materials. The results of Putri and Fitria [22] also showed a positive impact on student learning outcomes through the TAI learning model.…”
Section: Discussionmentioning
confidence: 99%
“…Pel laksanaan pel mbel lajaran matel matika dilakukan sel cara ol nlinel del ngan mel nel rapkan tel knol lol gi digital. Integrasi teknologi, seperti konferensi video, video animasi, kegiatan laboratorium, dan media interaktif, ke dalam model PBL telah terbukti berdampak positif pada kemampuan pemecahan masalah matematika siswa (Marhami et al, 2020;Daulay et al, 2019;Diana et al, 2022;Wilujeng et al, 2020).Sebagai contoh, penggunaan konferensi video selama pandemi Covid-19 ditemukan memiliki efek positif pada kemampuan pemecahan masalah matematika siswa (Marhami et al, 2020). Pel rkel mbangan ini diharapkan dapat tel rus mel ndol rol ng tel rsel lel nggaranya pel mbel lajaran yang baik sel rta tel rcapainya tujuan pel mbel lajaran sel suai del ngan NCTM.…”
Section: Pendahuluanunclassified
“…Kurangnya kemampuan siswa dalam mengerjakan soal matematika bisa disebabkan karena tidak menyimak dengan baik pembelajaran yang sedang berlangsung. Rendahnya kemampuan matematis siswa yang disebabkan oleh belum optimalnya penggunaan model pembelajaran membuat siswa kesulitan dalam memahami materi pembelajaran [9]. Hal ini disinyalir karena sulitnya pengembangan profesional terutama kompetensi pedagogis guru yang disebabkan oleh kurangnya dukungan dan inspirasi berkelanjutan dalam jangka panjang [10].…”
Section: Pendahuluanunclassified